2020
DOI: 10.1021/acs.joc.0c01299
|View full text |Cite
|
Sign up to set email alerts
|

Rearrangement of 7-Aryloxazolo[5,4-b]pyridines to Benzo[c][1,7]naphthyridine-4(3H)-ones and Thieno[3,2-c][1,7]naphthyridine-6(7H)-ones

Abstract: In this work, we describe the development of the rearrangement for 7-aryl-substituted oxazolo [5,4-b]pyridines treated with aluminum chloride into synthetically hard-to-reach benzo [c][1,7]naphthyridinones. The discovered rearrangement is applied to a variety of electron-rich (hetero)arene substrates. It offers the advantages of mild conditions (90 °C temperature), fast reaction rates (<4 h), compatibility with air moisture, and the use of inexpensive commercial reagents. The proposed reaction mechanism and ke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 53 publications
1
9
0
Order By: Relevance
“…As we previously reported, 7-aryloxazolo [5,4-b]pyridines or 4phenylbenzo[d]oxazoles are capable of rearrangement into benzo[c] [1,7]naphthyridin-4(3H)-ones or phenanthridin-4-ols when reacted with aluminum chloride. 3a,12a,b Oxazolo[5,4b]pyridine derivatives annulated at C(5)-C(6) position were not introduced into this reaction. We have found that heating oxazolo [5,4-b]pyrazolo [4,3-e]pyridines 5a-c, f-i in chlorobenzene to 130°C with a twofold excess of anhydrous AlCl3 leads to the formation of previously unknown benzo [c]pyrazolo [4,3-f] [1,7]naphthyridin-5-ones 7a-c, f, g, pyrazolo [4,3-f]thieno [3,2-c] [1,7]naphthyridin-6-one 7h or furo [3,2-c]pyrazolo [4,3-f] [1,7]naphthyridin-6-one 7i with yields of 42-82% (Scheme 3).…”
Section: Template For Synthesis Thiemementioning
confidence: 99%
“…As we previously reported, 7-aryloxazolo [5,4-b]pyridines or 4phenylbenzo[d]oxazoles are capable of rearrangement into benzo[c] [1,7]naphthyridin-4(3H)-ones or phenanthridin-4-ols when reacted with aluminum chloride. 3a,12a,b Oxazolo[5,4b]pyridine derivatives annulated at C(5)-C(6) position were not introduced into this reaction. We have found that heating oxazolo [5,4-b]pyrazolo [4,3-e]pyridines 5a-c, f-i in chlorobenzene to 130°C with a twofold excess of anhydrous AlCl3 leads to the formation of previously unknown benzo [c]pyrazolo [4,3-f] [1,7]naphthyridin-5-ones 7a-c, f, g, pyrazolo [4,3-f]thieno [3,2-c] [1,7]naphthyridin-6-one 7h or furo [3,2-c]pyrazolo [4,3-f] [1,7]naphthyridin-6-one 7i with yields of 42-82% (Scheme 3).…”
Section: Template For Synthesis Thiemementioning
confidence: 99%
“…It should be noted that the resulting benzo[c][1,7]naphthyridine system has not been synthesized until recently. 41,42 Scheme 2. Synthesis of benzo[c]isoquinoline[1,2-g][1,7]naphthyridine-5,7-diones 11a-f.…”
Section: Template For Synthesis Thiemementioning
confidence: 99%
“…It should be noted that the resulting benzo[c] [1,7]naphthyridine system has not been synthesized until recently. 41,42 Compounds 11a-f are poorly soluble in most organic solvents. In their 1 Н and 13 С NMR spectra, recorded in deuterotrifluoroacetic acid, there are no С(15)-H signals.…”
Section: Paper Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…In clinical practice, 5‐amino‐[3,4′‐bipyridin]‐6(1 H )‐one 4 , known as the cardiotonic drug Amrinone, is used [17] . In addition, 3‐aminopyridin‐2(1 H )‐ones are used in the synthesis more complex biologically active compounds [18a–m] …”
Section: Introductionmentioning
confidence: 99%